In vitro and in vivo evaluation of PEG-conjugated ketal-based chitosan micelles as pH-sensitive carriers. Issue 6 (17th December 2014) - Chen, Daquan; Sun, Jingfang
Abstract : Novel ketal-based PEGylated chitosan conjugates (PCK) were fabricated as pH-sensitive micelles for curcumin delivery which could be released at tumor pH conditions and show good behavior in vivo . Abstract : A novel ketal-based PEGylated chitosan conjugate, mPEG-Chitosan-Ketal (PCK), as a pH-sensitive drug carrier for cancer therapy, was found to have lower toxicity and to form self-assembled micelles for curcumin (Cur) delivery in our previous study. In this study, the PCK micelle encapsulated curcumin (Cur-PCK) with higher entrapment efficiency (EE) was prepared with an enhanced method with a smaller diameter of about 50 nm. An in vitro cellular uptake test indicated that the PCK micelles could be good intracellular carriers for anti-tumor drugs. Curcumin was incorporated into the PCK micelles not only as a therapeutic drug but also a fluorescence marker. Ex vivo imaging showed that the fluorescence signals of the PCK micelles in the liver and spleen were much higher from 5 h to 12 h, indicating that the PCK micelles improved blood circulation time and caused selective accumulation in the liver and spleen. Pharmacokinetic studies indicated that the PCK micelles had a long circulating time. In tissue distribution, the Cur-PCK micelles decreased in the following order: spleen > liver > heart > lung. In an in vivo anti-tumor efficacy assay, Cur-PCK micelles showed the most effective tumor inhibiting ability. These findings have shed some light on the PCK polymer as a potential pH-sensitive carrier of curcumin.